2011
DOI: 10.1016/j.joca.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs of rat articular cartilage at different developmental stages identified by Solexa sequencing

Abstract: Our study provided a unique opportunity to decipher how the elaboration of the miRNA repertoire contributes to the development process of articular cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 43 publications
(38 reference statements)
1
35
0
Order By: Relevance
“…In previous reports, miR-26a was on the list of the top 10% of miRNAs constitutively expressed at a high level in rat spleen [30], and also found to be considerable abundant in rat articular cartilage using Solexa sequencing from our previous study [31]. Its outstanding sufficiency in major immune organs and cartilage suggests its potential implication in arthritis development.…”
Section: Discussionmentioning
confidence: 81%
“…In previous reports, miR-26a was on the list of the top 10% of miRNAs constitutively expressed at a high level in rat spleen [30], and also found to be considerable abundant in rat articular cartilage using Solexa sequencing from our previous study [31]. Its outstanding sufficiency in major immune organs and cartilage suggests its potential implication in arthritis development.…”
Section: Discussionmentioning
confidence: 81%
“…In this context, it is of interest to review a study that identified microRNA profiles of rat articular cartilage at different developmental stages (194). Three small RNA libraries were constructed from the femoral head cartilage of Sprague-Dawley rats at postnatal day 0, day 21 and day 42 and sequenced by a deep sequencing approach.…”
Section: New Perspective Targets For Temporal Modulation In Cartilmentioning
confidence: 99%
“…There are several advanced methods to study the profile of miRNAs in OA from human and animals such as microarray, Solexa-based deep sequencing and next generation sequencing (NGS) [37-39]. Recently, Dr. Desjardin showed 609 and 622 miRNAs expression profiles in cartilage and bone, respectively, including 282 and 293 putative new miRNAs in cartilage and bone from equine [38].…”
Section: Resultsmentioning
confidence: 99%
“…Dr. Sun identified expression profiles of miRNAs of articular cartilage from rat femoral head cartilage. They made it possible to highlight 310 known miRNAs including 86 novel miRNAs candidates [39]. Current, we used NGS to analysis the miRNA expression profiles from articular cartilage and subchondral bone in normal, OA and OA+shockwave (SW).…”
Section: Resultsmentioning
confidence: 99%